2014
DOI: 10.1002/j.0022-0337.2014.78.2.tb05671.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Audit Teaching in Record–Keeping for Dental Undergraduates at International Medical University, Kuala Lumpur, Malaysia

Abstract: This study investigated the impact of clinical audit training on record-keeping behavior of dental students and students' perceptions of the clinical audit training. The training was delivered to Year 4 and Year 5 undergraduates at the School of Dentistry, International Medical University, Kuala Lumpur, Malaysia. It included a practical audit exercise on patient records. The results were presented by the undergraduates, and guidelines were framed from the recommendations proposed. Following this, an audit of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…Certain publications on clinical audit have demonstrated improved student record-keeping skills after an audit exercise and highlighted the importance of clinical audit as part of the curriculum. [23][24][25][26] The same has been reported by practices involving primary health care providers and dentists. 9,10 However, there is a dearth of information with regards to orthodontic patient care by undergraduate students.…”
Section: Discussionsupporting
confidence: 56%
“…Certain publications on clinical audit have demonstrated improved student record-keeping skills after an audit exercise and highlighted the importance of clinical audit as part of the curriculum. [23][24][25][26] The same has been reported by practices involving primary health care providers and dentists. 9,10 However, there is a dearth of information with regards to orthodontic patient care by undergraduate students.…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, in the most recent of the included studies, Chong et al presented robust evidence with seven of the ten record‐keeping domains identified demonstrating statistically significant improvements 13 . This research examined the compound effect of a short lecture, student research, peer review, and guidelines on record‐keeping expectations being placed in prominent positions.…”
Section: Resultsmentioning
confidence: 92%
“…Dental students and dental practitioners must continue to keep accurate records of all patient treatments to reflect how local regulations may have influenced patients’ experiences during the pandemic. Thus, conducting a routine clinical audit is a necessity in some dental institutions to improve patient oral care and service delivery, provide an opportunity for audit training, and identify areas that require improvement in the oral health care delivery system [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…One way to improve this is to provide dental students with a dental documentation template to record dental charts and establish consistency in dental record-keeping among the students. Clinical audit may be seen as a valuable teaching tool that helps improve students’ understanding of the importance of record-keeping and should be included in the undergraduate dental curriculum [ 16 ]. Additionally, it should be considered to establish a record-keeping policy for the teaching staff and conduct regular audits to ensure record-keeping standards are followed and maintained [ 2 ].…”
Section: Discussionmentioning
confidence: 99%